WAYS OF DEVELOPING GREEN INVESTMENTS (Conferencea, 2024)
Today, humanity is facing new threats. The world’s population continues to grow, while natural resources are constantly shrinking. It is said that such disproportion puts the countries of the world in a difficult situation. First of all, we are observing the aggravation of global environmental problems. Experts emphasize the need to introduce the principles of “green development” in the world economy in order to correct the situation. This approach is reflected in the UN Sustainable Development Goals.